Solving Indonesia's Health System Problem During Covid-19 Pandemic Through ASEAN Economic Community (AEC) - A.Nursyifa Az-Zahra; Andrew Mugi Wiyasa; Hugo Adventio; Tisya Nazwa Safira Lubis (Sociae Polites, 2022)
AEC has played an important role in many sectors, notably in the health and medical field. The urgency of an efficacious and adequate health system is becoming evident after COVID-19 pandemic ravaged the world. The lack of required health system is immensely faced by Indonesia, embroiled in the lack of medical workers and equipment. Previous studies claim that AEC can be a momentous relief for Indonesia’s problem on its health system. However, previous studies concerning this topic were solely focused on the supply of medical workers and all of them were published in pre-COVID 19 pandemic era. In this research, the authors study the analysis of AEC’s possible contribution to tackle the problems of Indonesia’s health system, which become much more intense as a consequence to COVID-19. This paper’s findings are acquired through qualitative methods by analyzing various secondary resources of books, journals, news, and government publications based on diagnostic research design. Through this, a diagnostic design will be used in this research by identifying the problems faced by Indonesia’s health system and analyzing whether AEC’s provisions are able to dispense effective cures. In this research, the authors found that Indonesia’s lack of medical equipment and pharmaceuticals products can be mitigated through ASEAN Medical Device Directives (AMDD) and policies created by the Pharmaceutical Product Working Group (PPWG). As in the “muddle” of Indonesia’s lack of medical workforces, AEC’s Mutually Recognized Agreements (MRAs) and the Movement of Natural Persons (MNP) Agreement ease the mobility of foreign nurses and doctors.